2016
DOI: 10.1158/1078-0432.ccr-15-2323
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Response of the MET/HGF Receptor to Small-Molecule Tyrosine Kinase Inhibitors Examined with Validated, Fit-for-Clinic Immunoassays

Abstract: Purpose: Rational development of targeted MET inhibitors for cancer treatment requires a quantitative understanding of target pharmacodynamics, including molecular target engagement, mechanism of action, and duration of effect.Experimental Design: Sandwich immunoassays and specimen handling procedures were developed and validated for quantifying full-length MET and its key phosphospecies (pMET) in core tumor biopsies. MET was captured using an antibody to the extracellular domain and then probed using antibodi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 52 publications
4
39
0
Order By: Relevance
“…In addition to difficulties in obtaining fresh tumor tissue to establish that MET diagnostics reflect the most recent status of cancer patients, two technical problems have hampered translation of pMET measurements in clinical studies: (I) sampling errors due to the limited stability of phospho-signals in biopsies; and (II) availability of specific antibodies and reagents that can be moved beyond the research setting into clinical laboratories. We recently described novel reagents and assays that the NCI has developed, standardized, and validated to facilitate the transition from the research lab to the clinic (13). In this review, we further elaborate on the underlying principles that guided development of our novel MET assays and the unique advantages they offer in providing tangible, quantifiable evidence of MET dysregulation and its blockade by MET inhibitors.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to difficulties in obtaining fresh tumor tissue to establish that MET diagnostics reflect the most recent status of cancer patients, two technical problems have hampered translation of pMET measurements in clinical studies: (I) sampling errors due to the limited stability of phospho-signals in biopsies; and (II) availability of specific antibodies and reagents that can be moved beyond the research setting into clinical laboratories. We recently described novel reagents and assays that the NCI has developed, standardized, and validated to facilitate the transition from the research lab to the clinic (13). In this review, we further elaborate on the underlying principles that guided development of our novel MET assays and the unique advantages they offer in providing tangible, quantifiable evidence of MET dysregulation and its blockade by MET inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…These studies could not identify MET peptides, likely because the enrichment process was insufficient to capture extremely low-abundance proteins. We studied the impact of both cold and warm ischemia time on SNU5 tumors and demonstrated that biopsies must be cryopreserved within three minutes of collection to preserve pMET signals (13). Even a modest delay of 15 minutes under warm/cold ischemia can result in >60% loss in pMET signal.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations